Efficacy of Dextrose Prolotherapy Compared with Intra-Articular Corticosteroids in Knee Osteoarthritis: A Systematic Review of Controlled Trials - Dimas Satrio Wicaksono; Ellena Rachma Kusuma; Elmawati Novit (Eduvest - Journal of Universal Studies, 2026)
Knee osteoarthritis (OA) is a leading cause of pain and disability in older adults worldwide. While intra-articular corticosteroid injections (IACIs) are widely used for short-term relief, dextrose prolotherapy has emerged as a regenerative alternative with potential for longer-term functional improvement, though direct comparative evidence remains limited. This study aims to systematically compare the clinical effectiveness of corticosteroid and dextrose prolotherapy injections in improving pain and physical function among knee OA patients. This systematic review followed the PRISMA 2020 statement. A comprehensive search of PubMed and ScienceDirect identified randomized controlled and prospective comparative trials published between January 2015 and October 2025, involving adults with radiographically or clinically confirmed knee OA reporting outcomes via validated scales (VAS, WOMAC, KOOS). Risk of bias was assessed using the Cochrane RoB 2.0 tool. From 724 records, 11 studies met inclusion criteria (six on prolotherapy, five on corticosteroids; sample sizes 40–484). Prolotherapy produced sustained pain and functional improvements at 8–12 weeks, persisting up to 6 months, while corticosteroids offered faster relief (1–4 weeks) but diminishing benefits after 3–6 months. Extended-release formulations (FX006, TLC599) provided modestly longer control. Both interventions were effective for mild-to-moderate knee OA; prolotherapy showed longer-lasting, safe, and cost-effective potential, warranting further high-quality trials.